Statistical analysis of divorce status and causes in the Russian Federation - A. M. Terekhov (Вестник университета)
The article presents the results of a statistical analysis of the breeding rate in Russia. The annual data characterizing the number of divorces in 2000−2021 are considered, unstable dynamics is noted, which is generally characterized by a tendency of their decline. The dynamics of the indicator according to short-term data has showed the presence of seasonal fluctuations, seasonality indices have been calculated, a seasonal wave graph has been constructed. Based on the analysis of sociological research data, the reasons for divorces have been identified. On the basis of statistical data, the indicators that have statistical links with the general coefficient of divorce are identified and have an impact on it. These variables have been grouped by individual characteristics, the following groups of factors are formed: demographic factors; income and employment; housing conditions; public health; digital environment. With the help of correlation and regression analysis, linear models have been built for individual groups of factors, and a generalised model. By comprehensively influencing the indicators included in the model, it is possible to adjust the values of the total dilution coefficient for the future. Based on cluster analysis, regions with high, medium and low breeding rates have been identified. The results of the study can be useful to state bodies in the framework of their practical activities.